Communicating architectural strategies (semiotics) - Susanti, Wiwik Dwi; Ikaputra (Talenta Publisher, 2024)
Semiotics is the science of signs aimed at communicating. In architecture, semiotics is a sign language that aims to provide information to society through architectural elements. Architectural semiotics consists of three elements: representation, user and meaning aimed at communication. The challenge in architectural semiotics is the process of delivering information that an architect wants to convey, whether it can be understood by an observer. Communication processes are not only limited to the process of understanding but capable of interpreting signs on architectural objects. To understand communicative architectural strategies, this study involves a case study of three architecture objects, which are then analyzed using semiotics. Gapura was chosen as an object of research, because it was a simple architectural object but had a load of meaning and signs. Research methods using the study of literature (journal, book and research report). The results of the research explained that the communication strategies of the three gaps were different, so architectural communications strategies were avoided by many things. (history, culture, identity dll). The architect's ability is tested to be able to communicate with the recipient through the signs he designs, so communication strategies and semiotic definitions are important to understand. Semiotics is the science of signs that aim to communicate. In architecture, semiotics is a language of signs that aims to provide information to the public through architectural elements. Architectural semiotics consists of three elements: representation, user and meaning, which aim to communicate.